Women's Perception Of The Benefits Of Fruit Or Vegetable-Based Hair Care Cosmetics To Solve Hair Problems - YULIA, ELVYRA (Jurnal Tata Rias, 2019)
This study aims to determine women's perceptions of the benefits of fruit and vegetable-based hair care cosmetics for addressing hair problems. The study population was all women of productive age, aged 17-45, who had previously received hair care treatments at home or at a beauty salon. A sample size of 30 respondents was selected. This research method was a survey, collecting quantitative data. Data were collected regarding housewives' perceptions of the benefits of fruit and vegetable cosmetics in hair care. Quantitative data were collected by distributing a questionnaire with closed-ended statements as the primary instrument to assess women's knowledge, views, and responses regarding the benefits of fruit and vegetable cosmetics in hair care. The research instrument used to determine women's perceptions used a Likert scale with a range of 1-4 levels. Responses ranged from very positive (scale 4) to very negative (scale 1). Instrument validity was determined using an r-table and then tested for reliability. The results of this study are expected to determine whether further socialization or education is needed to emphasize the importance of women's knowledge about using fruit and vegetable-based cosmetics for daily hair care.